1999
DOI: 10.1007/s004649901117
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller myotomy relieves dysphagia in achalasia when the esophagus is dilated

Abstract: In patients with achalasia who have esophageal dilation, a laparoscopic Heller myotomy and Dor fundoplication (a) took no longer and was no more difficult, (b) was associated with no more postoperative complications, and (c) gave just as good relief of dysphagia. We conclude that esophageal dilation by itself should rarely serve as an indication for esophagectomy rather than myotomy as the initial surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
2
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 15 publications
2
57
2
8
Order By: Relevance
“…Operation duration was 50-210 min. Median hospital stay was 2.6-8 d. One study [32] has reported the efficacy of HM for achalasia patients who failed combined treatment with PD and BoTx. The remission rate was 83%, operation duration was 156 min, and the hospital stay was 3.5 d. There were five [33][34][35][36][37] studies and two [38,39] studies that assessed the efficacy of HM for failed HM as the first-line treatment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Operation duration was 50-210 min. Median hospital stay was 2.6-8 d. One study [32] has reported the efficacy of HM for achalasia patients who failed combined treatment with PD and BoTx. The remission rate was 83%, operation duration was 156 min, and the hospital stay was 3.5 d. There were five [33][34][35][36][37] studies and two [38,39] studies that assessed the efficacy of HM for failed HM as the first-line treatment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Algunos cirujanos recomiendan la esofagectomía como tratamiento inicial 38,39 , mientras otros prefieren la miotomía, reservando la primera para aquellos pacientes con persistencia de los síntomas 38,39 . De esta forma, la miotomía laparoscópica puede representar una alternativa en el tratamiento de este grupo de pacientes 18,[38][39][40] . El paciente de esta serie que mantuvo un puntaje superior a 3 (puntaje posoperatorio de 6), es portador de un megaesófa-go.…”
Section: Discussionunclassified
“…Symptom improvement was reported in 89.3% and evidence of GEr in 14.9% of patients (9). Also in patients with significant esophageal dilation or megaesophagus, laparoscopic Heller myotomy and Dor fundoplication gives just as good relief of dysphagia (25). It is concluded that esophageal dilation by itself should rarely serve as an indication for esophagectomy rather than myotomy as the initial surgical treatment.…”
Section: Laparoscopic Myotomymentioning
confidence: 97%